Safety and efficacy of pembrolizumab in combination with S-1 plus oxaliplatin as a first-line treatment in patients with advanced gastric/gastroesophageal junction cancer: Cohort 1 data from the KEYNOTE-659 phase IIb study. (April 2020) - Kawazoe, Akihito; Yamaguchi, Kensei; Yasui, Hisateru; Negoro, Yuji; Azuma, Mizutomo; Amagai, Kenji; Hara, Hiroki; Baba, Hideo; Tsuda, Masahiro; Hosaka, Hisashi; Kawakami, Hisato; Oshima, Takashi; et al.
Abstract: Aim: The KEYNOTE-659 study evaluated the efficacy and safety of pembrolizumab in combination with chemotherapy as the first-line treatment in Japanese patients with advanced gastric/gastroesophageal junction (G/GEJ) cancer. In this paper, we report results from cohort 1 (S-1 plus oxaliplatin [SOX] with pembrolizumab). Methods: This was a non-randomised, multicentre, open-label phase IIb study in patients with advanced programmed death-ligand 1 (PD-L1)-positive, human epidermal growth factor receptor 2-negative G/GEJ tumours. The primary endpoint was the objective response rate (ORR) assessed by blinded independent central review (BICR). Secondary endpoints were duration of response (DOR), disease control rate (DCR), time to response (TTR), progression-free survival (PFS), overall survival (OS) and safety. Exploratory analyses were performed based on the PD-L1 combined positive score (CPS) status. Results: Fifty-four patients were evaluated. The median follow-up was 10.1 months. ORR and DCR by BICR were 72.2% (95% confidence interval [CI] 58.4–83.5) and 96.3% (95% CI 87.3–99.5), respectively. Median DOR, TTR, PFS and OS were as follows: not reached, 1.5 months, 9.4 months and not reached. The ORR was 73.9% in patients with CPS ≥1 to <10 and 71.0% in those with CPS ≥10. Grade ≥3 treatment-related adverse events (TRAEs) were reported by 57.4% of patients. The most common grade ≥3 TRAEs were decreased platelet count (14.8%), decreased neutrophil count (13.0%), colitis (5.6%) and adrenal insufficiency (5.6%). Conclusions: SOX with pembrolizumab showed encouraging efficacy and a manageable safety profile for the first-line treatment of advanced G/GEJ cancer. Trial registration: NCT03382600/JapicCTI-183829. Highlights: This study was conducted for gastric/gastroesophageal junction (G/GEJ) cancer. Efficacy and safety of S-1 + oxaliplatin (SOX) with pembrolizumab were assessed. Overall response rate assessed by blinded independent central review was 72.2%. No increase in treatment-related adverse events occurred with this combination. First-line SOX with pembrolizumab warrants further evaluation for G/GEJ cancer.